SISTEM INFORMASI PENGOLAHAN DATA ASPROV PSSI PROVINSI JAMBI: Asprov PSSI, Data Processing, Football, Information System, Information Technology, Waterfall Method - Adriana, Windy; Astuti, Reny Wahyuning; Ramadhan, Fajar; Windy Adriana (LP2M Universitas Nurdin Hamzah, 2025)
The rapid development of information technology and computers has influenced various aspects of life, including sports. In the context of football, data management is a crucial element in enhancing athlete performance and operational efficiency. The Provincial Association (Asprov) of PSSIJambi Province is currently facing challenges in managing data manually, often leading to errors and information loss. To address this issue, this research aims to design and develop a web-based